2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28493
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Engagement in Engineering Using Brain-Based Learning Principles as Instructional Delivery Protocols

Abstract: This paper presents a plausible solution using brain based learning principles as instructional delivery protocols to address the issue of lack of academic engagement among the upper level engineering students. The study was conducted at Tuskegee University, an HBCU and can be implemented universally in other institutes due to its foundation on brain based learning principles. Although student engagement issues inside engineering classrooms have several components, we focus our attention in this paper mainly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…The foundational deficiency and resulting disengagement can be particularly at play and self-perpetuating for students coming from underserved communities. An NSF-funded study performed at the mechanical engineering department at an HBCU school confirmed that foundational deficiency exists at upper level classes and this impedes engagement and their achievement of desired learning outcomes [16,17]. Mandating pre-requisite course has not been successful at preventing ill-prepared students from making their way to the upper level engineering courses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The foundational deficiency and resulting disengagement can be particularly at play and self-perpetuating for students coming from underserved communities. An NSF-funded study performed at the mechanical engineering department at an HBCU school confirmed that foundational deficiency exists at upper level classes and this impedes engagement and their achievement of desired learning outcomes [16,17]. Mandating pre-requisite course has not been successful at preventing ill-prepared students from making their way to the upper level engineering courses.…”
Section: Introductionmentioning
confidence: 99%
“…Using the principles of brain and learning sciences [18,19], Solomon et al [16] proposed a novel instructional framework titled "Knowledge and Curriculum Integration Ecosystem" (KACIE) to improve student engagement and learning outcomes. The framework is based on a set of systematic cognitive neuroscience learning procedures (we call them protocols) to be followed during classroom interactions and in designing and delivering instructional materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based at an HBCU-designated school with extensive support from the National Science Foundation (NSF), we have studied the phenomenon of the gap between our expectations and student performance in the mathematical competencies and preparation for advanced coursework [57][58][59]. As observed, such weaknesses connect to the level of student academic engagementboth inside and outside of the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…"Tailored Instructions and Engineered Delivery Using Protocols" (TIED UP) is a media-rich blended model used for teaching engineering concepts. Developed at Tuskegee University, this model is reported to be effective in improving student grades and their engagement in the classroom 19 . This model relies on the principles of brain-based learning [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%